Laser therapy for the treatment of pearly penile papules. Issue 1 (January 2017) - Maranda, Eric; Akintilo, Lisa; Hundley, Kelsey; Nguyen, Austin; Moore, Kevin; Zullo, Joseph; Jimenez, Joaquin
Abstract Pearly penile papules (PPP) present as dome-shaped papules of no more than 3 mm in diameter that line the base of the glans of the penis. These benign lesions affect between 14.3 and 48 % of men. While often asymptomatic, PPP can cause a great deal of psychological distress that may warrant treatment. Current treatment options include cryotherapy, electrodessication, and curettage (ED&C). However, these modalities may have considerable adverse cosmetic effects, including scarring, pain, and pigmentary changes. Laser modalities offer clear potential for improved cosmetic outcome in PPP treatment, but is not routinely used. Thus, a systematic review of available literature using the National Library of Medicine database PubMed was completed to find articles relevant to the treatment of PPP with laser and light therapy. The systematic search and screening of articles resulted in inclusion of eight articles discussing a total of 55 patients with PPP treated by laser therapy. The present systematic review found that erbium:yttrium-aluminum-garnet (Er:YAG) and CO2 laser were the most commonly reported (n = 45 and 7, respectively). Furthermore, the use of CO2, Er:YAG, pulsed dye laser, and fractional photothermolysis therapies demonstrated complete clearance of PPP in all cases with minimal complications and discomfort. Thus, based on the currently available evidence, laser therapy is a well-tolerated and efficacious method for treating PPP with minimal long-term adverse effects and a cosmetically desirable outcome. Although the included studies are limited in power, this systematic review offers clinically relevant insight into the potential for laser therapy.